معايرة معادلات مؤشر جودة الموقع لماكي السنديان العادي Quercus calliprinosWebb. على السفوح الشرقية للجبال الساحلية في سورية. - علي, وائل; زهوة, سليم; الشاطر, زهير; المحمود, فادي (Latakia University Journal -Biological Sciences Series, 2016)
This study aimed to calculate the site index of Palestine Oak grown on eastern versants of coastal mountains of Syriathrough calibration of some equations used in this field of study what helps foresters in the management of this type of vegetation.Age and top height of 287 dominant shoots from 102 sites of QuercuscalliprinosMaquis, distributed over the eastern versants of coastal mountains in Syria, have been measured. The sampled Maquis vary in their environmental conditions (altitude, slope, and aspect), their density, heights and ages as well.214 shoots (75% of dataset) were used for calibratingmodel constants (Chapman-Richards equation);the sum of least squares method (Ordinary Least Squares, OLS) was used to achieve that inExcel Solver. The remaining shoots (25% of dataset) were used for model statistical tests. The dominant tree height at age 40 years has been adopted as a reference. Model constants were estimated for three site classes (3, 4 and 5m). Values of R² were ranged between0.65 for the class (SI3) and 0.88 for the class (SI5). Values of Site index ranged between 3 and 5 m at the age of 40 years. These values are similar to that obtained for the same species at the western versants of the same mountains. Statistical tests of the model showed convincing results for Oak Maquis site index in the study area by calibrating Chapman-Richards equation.The calibrated equations for the three productivity classes of oak Maquisprovide an important tool for oak Maquis managers at the eastern versants of coastal mountains of Syria.هدف هذا البحث إلى تقدير مؤشر جودة الموقع لماكي السنديان العادي على السفوح الشرقية للجبال الساحلية في سورية من خلال معايرة بعض المعادلات الرياضية المستخدمة عالمياً في هذا المجال،مما يساعد الحراجيين في تربية هذه المجموعات الحرجية، وإدارتها بشكل مستدام.تم قياس العمر، والارتفاع الكلي لـ 287 فرعاً (خلفةً) من الأفرع الأضخم قطراً متوزعة على 102 موقعاً حراجياً، يسود فيها السنديان العادي بشكل ماكي،وتتباين في ظروفها البيئية (ارتفاع عن سطح البحر، وانحدار، ومعرض)، وفي كثافتها وأعمارها.تم استخدام 214 خلفة (75% من الأخلاف) من أجل معايرة ثوابت المعادلة المستخدمة (معادلة Chapman-Richards)بالاعتماد على مبدأ مجموع المربعات الصغرى لأخطاء الموديل (Ordinary Least Squares, OLS) باستخدام الحاللSolver في البرنامج Excel بينما تم استخدامبقية الأخلاف (25% من الأخلاف) لإجراء عدد من الاختبارات الإحصائية لجودة المعادلات المستخدمة.تم تقدير ثوابت المعادلة المستخدمة لثلاثة صفوف إنتاجية (3، 4، 5م)، وقد تم اعتماد الارتفاع السائد للأخلاف عند العمر المرجعي 40 عاماً.تراوحت قيم معامل التحديدCoefficient of Determination (R²) بين 0.65 لصف الإنتاجية الأول (SI 3) و0.88 لصف الإنتاجية الثالث(SI 5).وتباينت قيم مؤشر جودة الموقع لدى ماكي السنديان على السفح الشرقي للجبال الساحلية من سورية بين 3 – 5 مترعند عمر 40 عاماً وهي مشابهة لقيم هذا المؤشر للنوع نفسه على السفح الغربي للجبال الساحلية. أظهرت الاختبارات الإحصائية الحسابية والبيانية لجودة الموديل نتائج مقنعة لتقدير مؤشر جودة الموقع لماكي السنديان العادي في منطقة الدراسة بمعايرة معادلة Chapman-Richards.تشكلالمعادلات التي تمت معايرتها لصفوف الإنتاجية الثلاثةلماكي السنديان العادي أداةً مهمة لتربية ماكي السنديان العادي وإدارتها على السفوح الشرقية للجبال الساحلية في سورية.